Mobile beacon control algorithm that ensures observability in single range navigation*. Issue 23 (2016) - Mandić, Filip; Mišković, Nikola; Palomeras, Narcís; Carreras, Marc; Vallicrosa, Guillem
Abstract: Mobile beacon vehicles are used as navigational aid for autonomous underwater vehicles when performing navigation using single range measurements. They remove the constraints imposed on the underwater vehicle trajectory by executing trajectory that provides persistent range measurements. In this paper, control algorithm for beacon vehicle which ensures observability of the underwater vehicle's navigation filter is presented. It is characterized by small communication overhead, low computational complexity and it is deployable on both fully actuated and underactuated vehicles. The algorithm was tested in real-life environment and the acquired experimental results show that despite the presence of uncertainties and communication delays, the algorithm accomplishes its task.